An Analysis the Reasons Why Indonesia Administrators Commit Fraud - Hafiz, Muhammad Shareza; Halim, Abdul (Proceeding UII-ICABE, 2020)
Indonesia Corruption Watch (ICW) (2018) stated that at least there were cases of corruption that have been convicted at least 254 cases which involving State administrators in Indonesia which caused state losses of IDR 133.6 billion. The eradication of corruption in Indonesia has been enshrined in the law number 20 of 2001 which consists of 45 chapters that explained about the consequences of corruption but the level of the cases in Indonesia is still high in the executive, legislative and judicial levels. This research aims to identify and analyze the reason why Indonesia administrators commit fraud depend on the perception of academics in North Sumatra. The research was conducted by using a qualitative approach with case study. The data were collected by means of direct interviews that analyzed by using a thematic analysis. The research results show that there were several factors why the perpetrators commit fraud, namely lack of procedure, lack of control environment, financial pressure, and also work-related pressure. Keywords: Indonesia Administrator, Corruption, Abuse of Power, Pressure